Assisted Reproductive Technology Treatment, the Catalyst to Amplify the Effect of Maternal Infertility on Preterm Birth - Zhang, Youzhen; Zhou, Wei; Feng, Wanbing; Hu, Jingmei; Hu, Kuona; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Endocrinology, 2022)
Objective: To identify the influence of different infertility causes and assisted reproductive technology (ART) treatment on perinatal outcomes, and clarify the relationship between the maternal pathophysiological changes and artificial interventions. Methods: A total of 1629 fertile women and 27112 infertile women with sole infertility causes were prospectively recruited from July 2014 to December 2017, and 9894 singletons were finally enrolled into the study. Pregnancies with more than one cause of infertility and/or multiple births were excluded. According to the causes of infertility and ART treatment exposure, the participants were divided into four groups, namely fertile naturally conceived (NC) group, infertile NC group, female factor ART group, and male factor ART group. Perinatal outcomes, including gestational age of delivery (GA), birth weight (BW), preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA), and large for gestational age (LGA), were compared among groups. Logistic regression was performed to adjust several covariates. Result(s): The birth outcomes of the infertile NC group and fertile NC group, female factor ART group and infertile NC group were comparable. Compared to the fertile NC group, the female factor ART group had a shorter GA (39.0±1.6 weeks vs. 39.3±1.5 weeks, BW: P<0.05). An interaction test showed that ART treatment had an interaction on the effect of female infertility on GA (P=0.023). The female factor ART group also had a higher risk of PTB (OR 1.56, 95%CI 1.18-2.07) and LGA (OR 1.27, 95% CI 1.10-1.47) compared to the fertile NC group. The risk of PTB was increased for tubal factor ART (OR 1.49, 95%CI 1.12-2.00), ovulatory dysfunction ART (OR 1.87, 95%CI 1.29-2.72), and unexplained infertility ART (OR 1.88, 95%CI 1.11-3.17). The risk of LGA was increased for tubal factor ART (OR 1.28, 95%CI 1.11-1.48) and ovulatory dysfunction ART (OR 1.27, 95%CI 1.03-1.57). Conclusion(s): Our findings indicated that ART treatment could amplify the adverse effect of female infertility on neonates. Women with tubal factor infertility, ovulatory dysfunction, and unexplained infertility have a higher risk of PTB after ART treatment. Thus, clinicians should be vigilant in such patients and provide corresponding prevention strategies before and during pregnancy.